Urbanization and the Silent Suffering of the Elderly in Nepal - Kuikel, Jyoti; Sapkota, Rebisha; Aryal, Bhagwan (International Research Journal of MMC, 2025)
Nepal has experienced significant changes following dramatic urbanization. However, this process has failed to meet the needs of the elderly population, leaving them marginalized socially, mentally, and systematically. As a result, the study focuses on identifying the social, health-related, and system-related barriers faced by elderly individuals in Nepal. It reviews published articles, newspaper reports, and annual health records and presents its findings based on these secondary sources published between 2020 and 2025. The primary findings reveal that the elderly is socially isolated due to shifts in family dynamics. They suffer from both physical and mental health problems, and the health system has largely neglected their needs. Therefore, it is crucial to address these issues promptly so that the elderly can live healthy and fulfilling lives.